Clinical characteristics of subsequent histologically confirmed meningiomas in long-term childhood cancer survivors: A Dutch LATER study. (June 2021) - Verbruggen, Lisanne C.; Kok, Judith L.; Teepen, Jop C.; Janssens, Geert O.; de Boer, Charlotte M.; Stalpers, Lukas J.A.; Vernooij, Meike W.; van Dulmen-den Broeder, Eline; Loonen, Jacqueline J.; van den Heuvel-Eibrink, Marry M.; Tissing, Wim J.E.; van der Heiden-van der Loo, Margriet; et al.
Abstract: Background: Meningiomas are the most frequent brain tumours occurring after pediatric cranial radiotherapy (CrRT). Data on course of disease, to inform clinical management of meningiomas, are sparse. This study reports the clinical characteristics of histologically confirmed meningiomas in childhood cancer survivors (CCS) in the Netherlands. Methods: In total, 6015 CCS from the Dutch Long-Term Effects After Childhood Cancer (LATER) cohort were eligible, including 1551 with prior CrRT. These CCS were diagnosed with cancer age <18 y (between 1963 and 2002) and are not subject to brain tumour screening. We identified histologically confirmed meningiomas by record linkage with the Dutch Pathology Registry (PALGA; 1991–2018), and in the Dutch LATER registry. We extracted details regarding diagnosis, treatment, and follow-up from medical records. Results: We described 93 CCS with meningioma, of whom 89 (95.7%) were treated with CrRT (5.7% of 1551 with prior CrRT; OR = 68). Median age at diagnosis was 31.8 y (range: 13.2–50.5). Thirty survivors (32.3%) had synchronous meningiomas; 84 (90.3%) presented with symptoms. Only 16.1% of meningioma was detected at late effects clinics. Over time, all survivors had surgery; one-third also received radiotherapy. During follow-up 38 (40.9%), survivors developed new meningiomas, 22(23.7%) recurrences and at least four died due to the meningioma. Conclusions: Histologically confirmed meningiomas after childhood cancer are mostly diagnosed with symptoms and not during routine follow-up at late effects clinics. The meningiomas occur at a median of 20–25 y younger age than incidental meningiomas, are frequently multiple and recurrence after treatment is high. It is crucial to inform CCS and healthcare providers about risk and symptoms of subsequent meningiomas. Highlights: Histologically confirmed meningioma in childhood cancer survivors (CCS) are presented at young age with symptoms. Synchronous and metachronous meningiomas and recurrences are common in CCS. It is crucial to inform CCS and healthcare providers about risk and symptoms.